The study of potential evapotranspiration (PET) in UMP Gambang - Nor Afifah, Mohamad (2019)
Potential evapotranspiration (PET) is a term represents the combination of two processes water cycle whereby water is lost to the atmosphere from the soil and water bodies by evaporation meanwhile transpiration from vegetation or plant. PET is a complex and one of the most essential process in the hydrological cycle. It is useful to measure the atmospheric water demand of the region and hence could be used for various applications such as irrigation scheduling, drought monitoring, and crop production and understanding climate change impacts. The objectives of the study are to analyse the value of PET by using radiation-based methods; Penman-Monteith (PM) and Turc and temperature-based methods; Blaney-Criddle (BC) and Thornthwaite (TW) method in UMP Gambang and to evaluate the performance of PET estimation method. In this study, the comparison was made in term of values of PET by using Penman-Monteith, Turc, Blaney-Criddle and Thornthwaite methods with the exact PET values. It was found that radiation-based methods gave better performance compared to temperature-based methods in estimation of PET in the study. In radiation-based methods, PM method is the appropriate method to estimate PET in UMP Gambang with the highest accuracy of (R2 = 0.6447 for 2016, 0.6028 for 2017 and 0.6007 for 2018) and the lowest value of (RMSE = 0.3056 for 2017, 0.5836 for 2018) compared to the other methods.